Essentials of Hypertension The 120/80 paradigm - Fuchs, Flávio Danni (Springer International Publishing, 2018)
The main purpose of this book is to select and present the most essential information about hypertension. It aims to select all the more relevant data to guide the attitudes to prevent, diagnose, and treat hypertension. Hypertension accounts for more than 50% of deaths from stroke and ischemic heart disease worldwide. New blood pressure (BP) diagnostic thresholds for hypertension were released, which were set at 130/80 mmHg. As a consequence, millions of individuals in the world will be diagnosed as hypertensive, recognizing that they are at greater risk of presenting a CV event. Prevention and control of high BP will become the main focus for reducing the burden of CV disease, requiring a changing of cultural beliefs in some way similar to what happened in the last century with smoking. Strategies for prevention of the rising of BP with age, and the BP reduction in individuals already with high levels, are more complex than those related to smoking control. These strategies involve solid evidence to be implemented in populations. The extensive scientific literature dealing with hypertension and BP regulation is among the top dedicated to a single disease. The chapters and contents follow the clinical reasoning pathways. The characterization of the risks of high blood pressure is presented in the first chapter, discussing the evidence that led to changes in diagnostic thresholds and to the recommendations for maintaining BP within these limits in populations. Reasons for BP rising with age will follow, identifying the causes that must be fought to preventing the incidence of hypertension. Diagnosis of hypertension deserves a special chapter. The final chapter presents the fundamentals to select drug and non-drug therapies indicated in the prevention and controlling of high blood pressure.